PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN PASIEN BEROBAT DI RUMAH SAKIT HAJI MEDAN - Noni Defriani Kuswanti; Beby Karina Sembiring (Universitas Sumatera Utara, 2013)
Abstract: The result of the research from Significant simultaneous test (F-test) showed that simultaneously service marketing mix which consisted of the dimension of variables of product, price, promotion, location, people, process, and physical evidence had positive and significant influence on the patients’ decision to visit RS Haji, Medan. The result of t-test showed that partially the variables of product, process, and physical evidence had the most significant influence on the patients’ decision to visit RS Haji, Medan. Keywords: Service marketing Mix, Patients’ Decision